The effect of low-impact aerobic exercise in lowering total cholesterol levels - Ananta, Dyaz Surya; Yuniartika, Wachidah (Universitas 'Aisyiyah Yogyakarta, 2024)
Hypercholesterolemia (HC) is a disease caused by excessive fat consumption and a lack of physical activity. It can impact the emergence of various health disorders (e.g., heart disease, hypertension, and stroke). One of the non-pharmacological therapies to treat HC is by practicing low-impact aerobic. This study aims to determine the effect of low-impact aerobic exercise on decreasing cholesterol levels. Quasi-experimental research with a two-group pretest-posttest control group design. Purposive sampling was used in this study with inclusion criteria: patients with a cholesterol value >200 mmHg, who can do physical activity and do not take medication regularly. The sample, which comprised 64 respondents, was divided into intervention and control groups. The low-impact aerobic exercise intervention was conducted over a period of 8 weeks, with sessions held 2-3 times a week, each lasting 15 minutes. A glucose, cholesterol, uric acid (GCU) meter device was used to check cholesterol levels. Data were analyzed using a paired sample t-test. The mean decrease in cholesterol levels in the intervention group reached 55.22 mg/dl (from x̄ 245.13 mg/dl to x̄ 189.91 mg/dl). It was found a significant effect between low-impact aerobic exercise and reducing total cholesterol levels (p < 0.05). Low impact aerobic exercise intervention is cost-effective, has minimal side effects, and is effective in controlling and lowering cholesterol levels if done properly and intensively. Optimizing HC management can be done by combining HC interventions, e.g., diet, medication, and adequate physical activity. Further research on the optimization of HC management needs to be conducted.